2021
DOI: 10.1177/08971900211017867
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Variability With Insulin Glargine Versus Detemir in Hospitalized Patients With Diabetes

Abstract: Background: Prior research has demonstrated increased mortality with increasing glycemic variability (GV) in hospitalized patients with diabetes. Objective: We aimed to compare glycemic variability (GV) of insulin glargine to detemir in the inpatient setting. Methods: This single-center, retrospective, cohort study evaluated noncritically ill patients with diabetes on long-acting insulin at a large academic medical institution between 2010 and 2017. This study was reviewed and approved by the Institutional Rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…There is evidence that the glucose CV remains high in persons with diabetes treated with insulin glargine. An observational study of 1167 hospitalized persons with T1D and T2D treated with insulin glargine showed a glucose CV of 34.8%, 20 an outpatient continuous glucose monitoring study of 17 persons with T2D treated with insulin glargine 0.2 U/kg/day with 24‐h mean glucose 9.5 mmol/L showed glucose CV 26.8%, 21 and a study based on SMBG measured by 88 persons with T1D using insulin glargine as basal insulin showed the CV of the fasting and predinner glucose was 41.1% and 40.1%. 22 In considering the applicability to insulin prescription of the three levels of similarity defined by the FDA for biologics, then, one should realize that a given dose of insulin has highly variable expected action, reminding us of the dictum of Elliot Joslin in 1923, just 2 years after the discovery of insulin: “Insulin is a remedy primarily for the wise and not for the foolish, whether they be patients or doctors.” 23…”
mentioning
confidence: 99%
“…There is evidence that the glucose CV remains high in persons with diabetes treated with insulin glargine. An observational study of 1167 hospitalized persons with T1D and T2D treated with insulin glargine showed a glucose CV of 34.8%, 20 an outpatient continuous glucose monitoring study of 17 persons with T2D treated with insulin glargine 0.2 U/kg/day with 24‐h mean glucose 9.5 mmol/L showed glucose CV 26.8%, 21 and a study based on SMBG measured by 88 persons with T1D using insulin glargine as basal insulin showed the CV of the fasting and predinner glucose was 41.1% and 40.1%. 22 In considering the applicability to insulin prescription of the three levels of similarity defined by the FDA for biologics, then, one should realize that a given dose of insulin has highly variable expected action, reminding us of the dictum of Elliot Joslin in 1923, just 2 years after the discovery of insulin: “Insulin is a remedy primarily for the wise and not for the foolish, whether they be patients or doctors.” 23…”
mentioning
confidence: 99%